Extending the Theory of Planned Behavior: From Behavioral Intention to Collective Action - Lusia Vreyda Adveni; Umaimah Wahid; Ridzki Rinanto Sigit (Green Publisher Indonesia, 2026)
This study addresses the growing environmental challenges associated with waste management in Bali, Indonesia, where increasing tourism and urbanization contribute significantly to plastic pollution and ecological degradation. Despite the implementation of digital waste bank initiatives, limitations persist in understanding how individual behavioral intentions translate into sustained collective environmental actions. Therefore, this research aims to extend the Theory of Planned Behavior (TPB) by integrating cultural and social dimensions to better explain pro-environmental behavior in a collectivist context. A qualitative case study approach was employed, focusing on the digital waste bank social enterprise Griya Luhu. Data were collected through in-depth interviews, participant observation, and document analysis, and were analyzed using thematic analysis supported by NVivo software. This method enabled a comprehensive exploration of the interaction between behavioral intention, cultural values, and digital platforms. The findings reveal that while attitudes, subjective norms, and perceived behavioral control significantly influence behavioral intention, they are insufficient to ensure long-term participation. The cultural value of ngayah emerges as a key mediator, transforming individual intentions into collective commitments, while social reinforcement sustains participation through shared practices and community engagement. In conclusion, the study demonstrates that integrating cultural values and social mechanisms into TPB provides a more comprehensive framework for understanding and promoting sustainable collective action in environmental management.